2022
DOI: 10.1177/15357597221120348
|View full text |Cite
|
Sign up to set email alerts
|

Seizing Control of Neuronal Activity: Chemogenetic Applications in Epilepsy

Abstract: The fundamental commonality across pharmacotherapies for the epilepsies is the modulation of neuronal excitability. This poses a clear challenge—patterned neuronal excitation is essential to normal function, thus disrupting this activity leads to side effects. Moreover, the efficacy of current pharmacotherapy remains incomplete despite decades of drug development. Approaches that allow for the selective targeting of critical populations of cells and particular pathways in the brain have the potential to both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Chemogenetics can be employed to selectively modulate the excitability of neurons in vivo 47 . In the current study, we conducted chemogenetic manipulations to activate or inhibit GABAergic neurons in the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemogenetics can be employed to selectively modulate the excitability of neurons in vivo 47 . In the current study, we conducted chemogenetic manipulations to activate or inhibit GABAergic neurons in the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…This affects the transmission of information and reduces the degree of synchronization. In addition, due to the lack of effective control of seizures, the patient’s neuronal activity will appear as abnormal synchronicity and rhythmicity ( 13 ). Previous studies have found that different frequency bands are related to the symptoms of patients with epilepsy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…We utilized the Brain Connectivity Toolbox (BCT) to compute the graph theory metrics of each network ( 13 ). Graph theory metrics are employed to assess the brain network’s small-worldness, i.e., whether it exhibits a high degree of clustering and short characteristic path lengths, features that enhance the efficiency of information transmission within the network.…”
Section: Methodsmentioning
confidence: 99%
“…deschloroclozapine, DCZ), the optimization of the generally applied Adeno-Associated Virus (AAV) gene transfer method (virus dose-, titer-, promoter-and serotype selection), the proper toxicological evaluation in the nervous tissue, and the validation of appropriate proof of concept (POC) and " rst in vivo" methods to measure in vivo effectiveness quickly and reliably in rodent behavioral paradigms. Although the generation of in vivo chemogenetic POC studies has been started (e.g., in Parkinson's disease [9][10][11] or epilepsy [12][13][14]), the human translational validity of these pioneering studies is debatable, because of the above detailed methodological aws. Moreover, several high unmet need CNS indications would be potentially suitable targets for chemogenetic drug discovery [2], and more that are completely lacking the proper preclinical in vivo POC studies, including obesity, as a potential future target indication for chemogenetic therapies.…”
Section: Introductionmentioning
confidence: 99%